The time-varying evolution of inflation risks - Dimitris Korobilis; Bettina Landau; Alberto Musso; Anthoulla Phella (European Central Bank (ECB), 2021)
This paper develops a Bayesian quantile regression model with time-varying parameters (TVPs) for forecasting in ation risks. The proposed parametric methodology bridges the empirically established benefits of TVP regressions for forecasting in ation with the ability of quantile regression to model exibly the whole distribution of in ation. In order to make our approach accessible and empirically relevant for forecasting, we derive an efficient Gibbs sampler by transforming the state-space form of the TVP quantile regression into an equivalent high-dimensional regression form. An application of this methodology points to a good forecasting performance of quantile regressions with TVPs augmented with specific credit and money-based indicators for the prediction of the conditional distribution of in ation in the euro area, both in the short and longer run, and specifically for tail risks.
Keywords: C11; C22; C52; C53; C55; E31; E37; E51; 330; Quantile regression; MCMC; time-varying parameters; Bayesianshrinkage; Horseshoe; euro area; ination tail risks